Analysis of warehouse value-added services using pareto as a quality tool: A case study of third-party logistics service provider - Luay Jum'a; Muath Esam Basheer (Administrative Sciences, 2023)
The study aims to analyse warehouse value-added services (VAS) data for a third-party logistics (3PL) service provider, which leads to identifying service improvements and cost-cutting opportunities in performing VAS for clients using Pareto analysis as a quality tool. Using a case study approach, qualitative and quantitative data were collected from a leading 3PL firm in Belgium. The approach is conducted by applying major steps of Pareto analysis. Two pharmaceutical products were analysed according to medical general classification, namely narcotic analgesics (NA) and ophthalmic antihistamines and decongestants (OAD). The results showed that the Pareto principle is proven in the NA-ticketing case, and five activities consumed 83.3 percent of the total time of VAS operations. Furthermore, in the OAD-display case, the Pareto principle is proven and six activities were validated as they accounted for 81.26 percent of the total time of primary VAS operations. The study recommended a solution to each of the four causes of delay, including lack of training/best practices, inefficient space utilization, lack of automation, and lack of cohesiveness and planning. Despite the recognized importance of avoiding warehouse operation inefficiencies, the literature lacks studies applied to practice, and few contributions exist regarding analysing 3PL service providers' warehousing VAS operations data. This study identified all VAS activities for temperature-controlled pharmaceutical products. Moreover, the study proposes a warehouse operations improvement framework for non-automated 3PL warehouses and guides managers through Pareto analysis to cut costs and improve service level.
Keywords: 350; Pareto analysis; quality tool; third-party logistics; value-added services; warehouse data management